Rancang Bangun Alat Pengaduk Tahu Kapasitas 100 Liter/Proses - Syahputra, Beni; Gafur, Abdul (INOVTEK - SERI MESIN, 2023)
One of the typical Indonesian food products is tofu, tofu is a food that is always produced by the community which has become a hereditary culture, especially those produced by craftsmen in Rokan Hilir Regency. In the process of making tofu in Rokan Hilir Regency still uses a manual method of stirring, one of the stages in the process of making tofu is boiling soybean porridge. In addition to determining the quality of the product, the stirring process is also a stage that requires a lot of energy and time. In making tofu during the stirring process, it must always be stirred so that the mixture is evenly distributed, then so that there is no crust at the bottom. In addition, according to the partners, the stirring process greatly affects the tofu produced. Therefore the author makes a tofu stirring machine tool with a capacity of 100 liters / process which is able to stir the tofu with a time of 20 minutes / process. using an electric motor type 0.5 hp and a speed of 1450 pn. The design of this tool can be useful and help workers in the process of stirring tofu to make it faster and more efficient.Typical Keywords: Tofu Kneading Machine, Tofu or Soybean Processing, Typical Indonesia Food